Implementasi Pengadaan Transaksi Rutin dengan E-Catalogue di PT XYZ - Okta Armelya Rahim; Susan Febriantina; Maulana Amirul Adha (STIKes Ibnu Sina Ajibarang, 2025)
Digital procurement has significantly transformed business operations, impacting production, supply chain management, and customer interactions. At PT XYZ, routine commodity procurement utilizes an e-catalogue system, a form of e-procurement based on a catalog concept. This study examines the implementation stages, advantages, disadvantages, and challenges of the system. Using a qualitative descriptive method, data was collected through interviews, observations, and documentation.Findings indicate that e-catalogue implementation at PT XYZ is complex before achieving full operation. Key advantages include automated PR creation and PO release, reducing administrative workload, enhancing transparency, and expediting procurement. However, drawbacks include inefficient data updates, a less user-friendly interface, and frequent system errors. Challenges involve poor socialization and the perception that the system mainly benefits buyers. Moreover, limited user understanding of time efficiency and error reduction further hinders adoption. Overall, while e-catalogue improves procurement efficiency, further enhancements in user training, system reliability, and feature usability are needed for optimal performance.